Is pre-consultation conducted by the assistant physician effective in improving online healthcare service quality and satisfaction? - ZHAO, Anqi (Institutional Knowledge at Singapore Management University, 2023)
To improve online healthcare quality and efficiency, online healthcare communities (OHCs) enabled the pre-consultation function, in which an assistant physician interacts with the patient to understand and document the patient’s health conditions, medical history, and consultation objectives prior to the formal online consultation with the attending physician. Using detailed service data from a Chinese OHC, this study scrutinizes the effect of using pre-consultation on online healthcare service quality and satisfaction. The results show that pre-consultation can significantly increase the attending physician’s response speed, length, and the level of informational support embedded within the response, while maintaining a consistent level of emotional support. Despite the improvement in service quality, pre-consultation leads to decreased patient satisfaction with the consultation service. Furthermore, we find that pre-consultation improves service quality by enhancing the professionalism and comprehensiveness of patient case information and reducing information seeking and clarification of the attending physician with the patient.